Shifts in northern Arizona plant and insect pollinator communities between 2 years with substantially different precipitation totals - P. R. Chesshire; P. R. Chesshire; L. M. Holeski (Web Ecology)
The structure of plant–pollinator mutualistic interactions is important for pollination network stability and robustness in the face of environmental change. Even slight changes in seasonal or annual precipitation patterns can disrupt the critical plant–pollinator mutualisms that comprise healthy pollination systems, primarily through changes in the availability of floral resources. Increased instances of drought across regions, especially in the southwestern United States, are a likely threat to plant and pollinator species richness, phenology, and mutualistic associations. In this paper, we evaluated temporal changes in plant–pollinator communities of the San Francisco Peaks in northern Arizona between 2 years with substantially different cumulative precipitation totals. Specifically, we evaluated how plant and pollinator species abundance, richness, mutualistic interactions, and degree of pollinator generalization differed between 2 years, which we refer to as the “wet year” (2017) and “dry year” (2018), and how these shifts may be further impacted at three different life zones (elevation zones). We determined that plant species richness decreased in the dry year across all life zones, and at the highest life zone, Spruce Fir, overall pollinator species generalization increased in the dry year, with a larger number of species considered to be “core generalists”. Additionally, the timing of plant and pollinator activity periods was less consistent in the dry year; there was delayed blooming for many floral resources until after monsoon rains began, and insect activity tended to start and continue later in the season for all life zones. A greater number of pollinator species considered to be core generalists in the dry year at this highest life zone despite fewer floral resources until later in the season may suggest some degree of plasticity when it comes to partner choice, which may be buffering this pollination system from community collapse when resources are scarce. With changing climate, including unpredictable precipitation worldwide, studies to uncover which pollinator species and plant–pollinator associations are most critical for community stability in drier conditions are important for informing conservation decisions on local scales.